(untitled) (Superficies y Vacío, 2024)
The setting and hardening of cement paste can be taken as the progressive hydration reaction of cement. This paper reports the findings on setting time of cement paste at early hydration by using a novel method named relative electrical impedance (REI). The novel REI method measures the relative electrical impedance between electrodes (ring shaped) embedded in the cement paste. REI measurements were conducted on cement paste samples with a water-cement ratio of 1:2 over 24 hours. REI measurements were compared with VICAT and heat latent methods for indirect validation. It was found that the proposed REI technique determined the 4 periods of the setting time process (sleeping, hydration, deceleration, and diffusion) and allowed the measurement of the sleeping period in detail. It was concluded that the novel REI method could be used as a new method to measure the setting time of cement paste in early hydration.